Leaf Mineral Composition of Coffee Infected by a Hemileia vastatrix Fungus in Bondowoso, East Java - Erwin Prastowo; Novie Pranata Erdiansyah; Rina Arimarsetiowati (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2019)
Leaf rust disease caused by Hemileia vastatrix fungus may become an important issue on highland coffee (Coffea arabica) especially related to the progressive increase in terms of global temperature. A research aimed at evaluating the mineral composition of some rusted coffee leaves from a single clone S 795 was carried out in Andungsari Experimental Station, Indonesian Coffee and Cocoa Research Institute. A single block experiment was situated at 1451 m asl. The intensity of rust spot in the leaves were identified, and estimated to correspond with the score of 5 to 7 out of 10. The difference in the nutrient status between normal and rusted leaves were statistically evaluated by comparing the mean values using unpaired t-test. The leaf analysis shows an optimal range for potassium (K), calcium (Ca), magnesium (Mg) and silicon (Si). Silicon distribution exhibits a high vari- ability with coefficient of variation (CV) around 30%, while K is slightly lower with CV less than 10%. Principal component analysis shows that Ca, Mg and K may have explained the most variation in the original variables as defined by PC1 (54.76%), PC2 (23.22%), and PC3 (14.01%). The rusted leaves are associated with Ca and Si while normal leaves are associated with K. A considerable high of K may explain for the depression of Ca in normal leaves which is, however, associated with an antagonism between these two minerals. The ratio of has a negative correlation with Ca, and may show a potential as an indicator for leaf mineral evaluation in the context of Hemileia vastatrix fungus infected coffee.